2016
DOI: 10.1111/jgh.13297
|View full text |Cite
|
Sign up to set email alerts
|

Mouse models for gastric cancer: Matching models to biological questions

Abstract: Gastric cancer is the third leading cause of cancer‐related mortality worldwide. This is in part due to the asymptomatic nature of the disease, which often results in late‐stage diagnosis, at which point there are limited treatment options. Even when treated successfully, gastric cancer patients have a high risk of tumor recurrence and acquired drug resistance. It is vital to gain a better understanding of the molecular mechanisms underlying gastric cancer pathogenesis to facilitate the design of new‐targeted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 181 publications
(352 reference statements)
0
35
0
Order By: Relevance
“…Next, we infected the TGF‐β ∆DC mice and TGF‐β fl/fl mice with H. felis (10 8 CFU/mL H. felis via gavage 3 times over 5 days). H. felis was used as it produces more severe gastritis in mice and achieves higher levels of colonization compared to H. pylori 32‐34 . Our data show that after 6 months of H. felis infection, TGF‐β ∆DC mice developed more severe gastritis compared to control TGF‐β fl/fl mice, as evidenced by increased neutrophils, gland distortion, and metaplasia.…”
Section: Resultsmentioning
confidence: 85%
“…Next, we infected the TGF‐β ∆DC mice and TGF‐β fl/fl mice with H. felis (10 8 CFU/mL H. felis via gavage 3 times over 5 days). H. felis was used as it produces more severe gastritis in mice and achieves higher levels of colonization compared to H. pylori 32‐34 . Our data show that after 6 months of H. felis infection, TGF‐β ∆DC mice developed more severe gastritis compared to control TGF‐β fl/fl mice, as evidenced by increased neutrophils, gland distortion, and metaplasia.…”
Section: Resultsmentioning
confidence: 85%
“…Animal models have been extensively used to study the pathogenesis and metastatic mechanisms of gastric cancer and play an extremely important role in the evaluation of the efficacy and toxicity of therapeutic drugs [8][9][10]. At present, gastric cancer animal models mainly include the following: the induction model, the transplantation model, and the genetic engineering model [11]. Among the three types of models, the transplantation model is easily operated and thus widely used.…”
Section: Discussionmentioning
confidence: 99%
“…Among the three types of models, the transplantation model is easily operated and thus widely used. The type of experimental animals, tumor xenografts, and the site and route of transplantation have been considered factors that affect the success of xenograft models [11]. Mice with defects in immune function, such as nude mice and mice with severe combined immunodeficiency (SCID), are commonly used for xenograft models [11,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some years later, using the same animal model it was confirmed that colonization with H. pylori can lead to the development of gastric cancer [ 21 ]. More recently, a report summarized the findings of several investigators who had developed a mouse model of gastric cancer in which H. pylori challenges were associated with the development of gastric cancer [ 22 ]. This model represents a major step forward in the study of H. pylori and its role in gastric cancer.…”
Section: Is H Pylori a Risk Factor Or A True Cmentioning
confidence: 99%